Strategic Planning and Human Capital Plan in Bina Insani University Business Development Project at Cikarang Campus - Novita Sari Enny Astuti; Tantri Yanuar Rahmat Syah; Suwarto; Rhian Indradewa (Syntax Corporation Indonesia, 2024)
Bina Insani University is one of the leading private universities in Indonesia. The development of Bina Insani University's business project on the Cikarang campus requires a large investment, both in terms of financial and human resources. Therefore, careful strategic planning is needed to ensure the success of the business development. The purpose of this study is to examine the strategic planning and human capital plan in the business development project of Bina Insani University on the Cikarang campus. This research uses qualitative research methods. Data collection techniques in this study used literature studies and observation. The data that has been collected is then analyzed thematically. The results showed that the strategic planning and human capital plan in Bina Insani University's business development project at the Cikarang campus had been carried out carefully. Strategic planning is done by establishing the long-term, input stage, the matching stage, the decision stage, the business level, and the lean business canvas model. The human capital plan is done with the stages of goals and objectives, corporate culture and values, organizational structure, human capital planning, and Human Resources Cost Projections.